The Impllementation of the Use of the Village Financial Sysytem (SISKEUDES) APPS in Tomini in Tomini Sub-District of Bolaang Mongondow Selatan Regency - Abidin Patilima; Sri Yulianti Mozin; Djamila Podungge (LP2M Universitas Bina Mandiri Gorontalo, 2021)
The present study aims to determine and analyze the implementation of the use of the SISKEUDES application in villages of Tomini sub-district of Bolaang Mongondow Selatan regency. It also aims to determine and analyze the factors that determine the implementation of the use of the SISKEUDES application in villages of Tomini sub-district of Bolaang Mongondow Selatan regency. This study is a qualitative research using a descriptive-explanatory case study approach, which is to examine, analyze and describe the results of the study. As the results, the study shows that the stages of village financial management in Tomini sub-district in accordance with Permendagri Number 20 of 2018 concerning Village Financial Management in terms of planning, implementation aspects, administration, reporting, and accountability aspects. Furthermore, the factors that determine the management of village funds in Tomini sub-district are human resources and internet networks.